Implementing the Cooperative Learning Model Team Game Tournament Type in Improving Studentsâ€™ Vocabulary at MTSN Nurul Falah Jambi - Munawwaroh, Khidayatul; Pratiwi, Rimeira Nadya; Rahmawati, Suci (Universitas Batanghari Jambi, 2022)
The purpose of the research was to improve studentsâ€™ vocabulary ability through cooperative learning model Teams Game Tournament type at second year students of MTs NurulFalah Jambi. The target of this research is hoped that cooperative learning model teamsâ€™ game tournament type can be one of model that can be used by the English teacher in teaching vocabulary. This research used classroom action research. This research conducted in MTs NurulFalah Jambi, and the subject of research was the second-year students with total of student are 34 students in academic year 2018/2019. The researcher used observation, test, and questionnaire to get the data. The procedure in this research is referring to classroom action research that consists of four elements: planning, acting, observing, and reflecting which did in every cycle. The researcher did cycle 1, and then the researcher arranged the action plan on the result of the reflection at the first cycle. There was the improvement of studentsâ€™ vocabulary ability, the test score at cycle 1 was 14,49% and at cycle 2 was 31,54 %. There are 6 teams, 3 teams got the award as â€œSuper teamâ€ they are group 3, 4, and 5. 2 Teams got the award as â€œGreat Teamâ€ they are group 2 and 7. While 2 teams got the award as â€œGood Teamâ€ they are group 1 and 6. This research has revealed that Cooperative Learning Model Team Game Tournament Type can be an alternative to solve the studentsâ€™ problems in vocabulary.